BLOOM’S TAXONOMY ON READING EXERCISES IN ENGLISH TEXTBOOK “ BAHASA INGGRIS” FOR GRADE TEN SENIOR HIGH SCHOOL STUDENTS - Chintia Theresia; Johannes Jefria Gultom; Tiarnita Maria Siregar (Universitas Negeri Medan, 2021)
BLOOM’S TAXONOMY ON READING EXERCISES IN ENGLISH TEXTBOOK “BAHASA INGGRIS” FOR GRADE TEN SENIOR HIGH SCHOOL STUDENTS*Chintia Theresia**Johannes Jefria Gultom,S.Pd.,M.Hum.**Tiarnita Maria Sarjani Siregar,S.Pd.,M.Hum.ABSTRACTTheresia,Chintia. Registration Number: 216121006. Bloom’s Taxonomy on Reading Exercises inEnglish Textbook “Bahasa Inggris” for Grade Ten Senior High School. A Thesis, EnglishEducation Study Program, Faculty of Languages and Arts,Universitas Negeri Medan,2020.The purpose of this study was to find the types of reading exercises and the distribution of Bloom’s Taxonomy incognitive domain in the third revision of English Textbook for grade ten Senior High School students published byPusat Perbukuan dan Kurikulum . Based on Revised version of Bloom’s Taxonomy (2001) there are 3 domain inBloom Taxonomy such as the cognitive domain, affective domain and psychomotor domain. This study focused oncognitive domain. There are six level of cognitive domain; remember, understand, apply, analyze, evaluate andcreate. Based on Heaton Theory, there are 5 types of reading exercises. Namely, matching test, true false, multiplechoice, completion item, and open ended. This study used the qualitative method to solve the problems. The data ofthis study were taken from 172 questions from 30 reading exercises. For collecting the data this study used onetechnique, that is documentation. Analysis technique used which were data reduction, data displays and conclusiondrawing/ verification. The finding of this study are there are 43% for remember, 32% for understand, 5% for apply,15% for analyze, 3 % for evaluate, and 2 % for create. There are 3 of 5 types of question used in this textbook.Keywords : Bloom’s Taxonomy, Cognitive Domain, Questions, Reading,